2022
DOI: 10.1101/2022.06.14.496052
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural basis for the unique multifaceted interaction of DPPA3 with the UHRF1 PHD finger

Abstract: Ubiquitin-like with PHD and RING finger domain-containing protein 1 (UHRF1)-dependent DNA methylation is essential for maintaining cell fate during cell proliferation. Developmental pluripotency-associated 3 (DPPA3) is an intrinsically disordered protein that specifically interacts with UHRF1 and promotes DNA demethylation by inhibiting UHRF1 chromatin localization. However, the molecular basis of how DPPA3 interacts with and inhibits UHRF1 remains unclear. We aimed to determine the solution nuclear magnetic r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
(103 reference statements)
0
1
0
Order By: Relevance
“…Alternatively, as it has been reported that UHRF1 and HELLS interact (25), this HELLS enrichment on ∆DNMT1 extract could be caused by chromatin enrichment of UHRF1, which directly binds hemimethylated DNA (30)(31)(32). To distinguish between these possibilities, we used recombinant mouse DPPA3 (mDPPA3), which binds to UHRF1 and inhibits its association with chromatin (51)(52)(53). In control egg extracts, DNMT1, UHRF1, HELLS and CDCA7e (a sole CDCA7 paralog present in Xenopus eggs) transiently associated with chromatin in S phase min after sperm nucleus addition to egg extracts) (Fig.…”
Section: Inhibiting Maintenance Dna Methylation Enriches Hells and Cd...mentioning
confidence: 99%
“…Alternatively, as it has been reported that UHRF1 and HELLS interact (25), this HELLS enrichment on ∆DNMT1 extract could be caused by chromatin enrichment of UHRF1, which directly binds hemimethylated DNA (30)(31)(32). To distinguish between these possibilities, we used recombinant mouse DPPA3 (mDPPA3), which binds to UHRF1 and inhibits its association with chromatin (51)(52)(53). In control egg extracts, DNMT1, UHRF1, HELLS and CDCA7e (a sole CDCA7 paralog present in Xenopus eggs) transiently associated with chromatin in S phase min after sperm nucleus addition to egg extracts) (Fig.…”
Section: Inhibiting Maintenance Dna Methylation Enriches Hells and Cd...mentioning
confidence: 99%